Liquid exfoliation of Ni2P2S6: structural characterization, size-dependent properties, and degradation - Synnatschke, Kevin; Hofstetter, Yvonne J.; Grieger, Sebastian; Vaynzof, Yana; Backes, Claudia (Chemistry of materials, 2019)
Reducing the size of a material, from a bulk solid to a nanomaterial, may lead to drastic changes of various properties including reactivity and optical properties. Chemical reactivity is often increased due to the nanomaterial’s higher effective surface area, while confinement and geometric effects lead to systematic changes in optical properties. Here, we investigate the size-dependent properties of Ni2P2S6 nanosheets that were obtained from liquid phase exfoliation in N-cyclohexyl-2-pyrrolidone. The as-obtained stock dispersion was size-selected by liquid cascade centrifugation resulting in fractions with distinct size and thickness distributions, as quantified by statistical atomic force microscopy. Raman, TEM, XRD, and XPS characterization revealed that the exfoliated flakes have good crystallinity and high structural integrity across all sizes. The optical extinction and absorbance spectra systematically change with the lateral dimensions and layer number, respectively. Linking these changes to nanosheet dimensions allows us to establish quantitative metrics for size and thickness from optical properties. To gain insights into the environmental stability, extinction/absorbance behavior was followed as a function of time at different storage temperatures. Degradation is observed following first-order kinetics, and activation energies were extracted from the temperature dependent data. The decomposition is due to oxidation which appears to occur both at edges and on the basal plane.